The Effects of Façade Design and Building Orientation on Indoor Air Temperatures in Campus Building: Case Study - Wenny Arminda; Maqbul Kamaruddin; M. Shoful Ulum; Widi Dwi Satria; Nurul Oktaviani (Center for Scientific Publication, 2024)
As it serves as the outermost layer directly exposed to the surrounding climate, building façade is one of the key factors influencing thermal comfort. Glass is a commonly used facade material in building design due to its ability to allow natural light into indoor spaces and enhance aesthetic appeal. However, if the proportion of glass is not carefully considered in relation to the local climate—particularly the building’s orientation to the sun— it can lead to increased indoor temperatures, negatively impacting thermal comfort. This study examines the impact of facade design, specifically the window-to-wall ratio (WWR) and building orientation, on indoor air temperatures in two case study buildings at Institut Teknologi Sumatera: Building E and the General Lecture Building (GKU). Field measurements conducted over six consecutive days, with hourly temperature recordings, showed that GKU consistently maintained lower indoor temperatures than Building E. This was attributed to GKU’s north-south orientation and its brick facade with shading elements, which helped minimize solar heat gain. In contrast, Building E, characterized by an east-west orientation, a high WWR, and insufficient shading, experienced higher indoor temperatures and thermal discomfort, even with air-conditioning. These findings highlight the crucial role of facade design in optimizing thermal performance in tropical climates, offering valuable insights for sustainable architectural practices worldwide.